On psychological and war mission of the founder of the Lvov-Warsaw School - RZEPA, TERESA (Studia Psychologica: Theoria et praxis, 2016)
The double mission, ideally fulfilled by Kazimierz Twardowski, the founder of the Lvov-Warsaw School, is discussed in the article. Twardowski fulfilling his psychological mission all his life while the war mission lasted three years (1914–1917), when he was carrying out the role of the president (rector) of the Lvov University. A short biography of Kazimierz Twardowski precedes the descriptions of those missions.